The Influence of the Problem-Based Learning Model on Knowledge Competence and Critical Thinking Skills of Students at Madrasah Aliyah BPD Desa Iha, Huamual District, West Seram Regency, Regarding Conflict - Hallatu, Yosepus; Lasaiba, Mohammad Amin (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2022)
This study aims to determine the influence of the problem-based learning model on students' knowledge competence and critical thinking skills regarding inter-village conflict. The research design used is an experimental design with a pretest-posttest randomized control technique. The research population includes all 11th-grade classes at Madrasah Aliyah BPD (Village Management Agency) Iha, Maluku Province, which consists of three courses. The sample consists of two classes: XI 2, as the experimental class implementing the problem-based learning model, and XI 3, as the control class implementing the direct instruction model. The analysis of students' knowledge competence and critical thinking skills was conducted using a t-test. The results show that the descriptive analysis indicates that the problem-based learning model effectively enhances students' knowledge competence and critical thinking skills based on the following factors: (1) student activity levels are categorized as active, and (2) learning outcomes mastery is achieved. It is evidenced by a significance value of 0.000 ≤ 0.05 and a t-value (5.637) ≥ t-table (1.688). It indicates that there is a significant difference in the post-test mean scores, with the problem-based learning model being more effective than the direct instruction model in improving knowledge competence and critical thinking skills.